Value of endometrial echo pattern transformation after hCG trigger in predicting IVF pregnancy outcome: a prospective cohort study - Zhaojuan Hou; Qiong Zhang; Jing Zhao; Aizhuang Xu; Aihua He; Xi Huang; Shi Xie; Jing Fu; Lan Xiao; Yanping Li (BMC, 2019)
Abstract Background There is much value in identifying non-invasive ways of measuring endometrial receptivity, as it has the potential to improve outcomes following in vitro fertilization (IVF). It has been suggested that endometrial echogenicity on the day of hCG administration was a good marker of endometrial receptivity. In the daily practice, we notice that patients with non-homogeneous hyperechoic endometrium on the embryo transfer day usually have lower pregnancy rates. We therefore extended the research onward transformation of echo pattern after hCG trigger to analyze the relationship between endometrial echogenicity transformation and IVF outcomes. Methods A total of 146 infertile women undergoing their first IVF cycle were recruited in the prospective cohort study from August 2017 through August 2018. A series of endometrial echo pattern monitoring was carried out in these patients after hCG trigger: hCG day, from 1 through 3 days after ovum pick-up (OPU + 1, OPU + 2, OPU + 3). Results The endometrial echogenicity value was calculated as the ratio of the hyperechogenic endometrial area over the whole endometrial area. Clinical pregnancy rate and embryo implantation rate had positive relationship with echogenicity value. The ROC curve analysis of endometrial echogenicity showed the area under curve was greatest on the second day after oocyte retrieval (OPU + 1, 2, 3 were 0.738, 0.765, 0.714 respectively) versus pregnancy. Endometrial echogenicity value on OPU + 2 had a higher predictive efficiency, and the cutoff value was 76.5%. The sensitivity was 61.3% and specificity was 82.0%. When putting the cut-off at <60%, the sensitivity was 93.8% and the specificity was 23.1%. Conclusions The endometrial echogenicity value on OPU + 2 was recommended to evaluate endometrial receptivity. It seemed appropriate for clinicians to provide a 'freeze all' IVF cycle and transfer in a subsequent frozen-thawed embryos cycle when echogenicity value <60% on OPU + 2. Trial registration The registration number was ChiCTR-OOC-17012214 and the registration date was August 1st, 2017.